2012
DOI: 10.1155/2012/673132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Berberine and Hwangryunhaedok-Tang on Oral Bioavailability and Pharmacokinetics of Ciprofloxacin in Rats

Abstract: Hwangryunhaedok-Tang (HR) and berberine-containing single herbs are used to treat bacterial infection and inflammatory diseases in eastern Asia. The combination of berberine-containing herbal medicines and ciprofloxacin can be an excellent antibacterial chemotherapy against multidrug resistance bacteria. To evaluate the pretreatment effect of berberine and HR, vehicle, berberine (25 and 50 mg/kg/day), and HR (1.4 g/kg/day) were daily administered to rats for five consecutive days. On day 6, ciprofloxacin was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In rats, the reported absolute oral bioavailability of CFX was 69.9% at a dose of 20 mg/kg [ 85 ]. In contrast, another group reported that the oral bioavailability of CFX was 19.87% when administered at a dose of 20 mg/kg in rats [ 88 ]. This reported value (19.87% in rats) is the same as the present results obtained in EDTA-treated rabbits (19.37 ± 2.28%) as shown in Table 9 .…”
Section: Discussionmentioning
confidence: 99%
“…In rats, the reported absolute oral bioavailability of CFX was 69.9% at a dose of 20 mg/kg [ 85 ]. In contrast, another group reported that the oral bioavailability of CFX was 19.87% when administered at a dose of 20 mg/kg in rats [ 88 ]. This reported value (19.87% in rats) is the same as the present results obtained in EDTA-treated rabbits (19.37 ± 2.28%) as shown in Table 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, it is well-known that spinach is rich in minerals, such as Ca, Mg, Fe and Al. 32) For preparation of thylakoid-rich spinach extract, Appethyl ® , reagents containing these metals are not used. 12) Thus, we speculate that these metals in the thylakoid-rich spinach extract are derived from spinach itself.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, mixed extraction with decoction and distillation of HRHD-D was shown to demonstrate higher anti-inflammatory activity then distillation only. A major ingredient of Copris japonica, berberine, and a main ingredient of Phellodendron amurense, palmatine, are alkaloids whose anti-inflammatory properties of cortex phellodendri amurensis in vitro and in vivo may explain its utility for attenuating inflammationrelated diseases and effectively inhibiting bacteria, fungi and viruses 18,19) . Additionally, it was reported by Peng et al 20) that Gardenia jasminoides(Schisandra chinensis) showed strong inhibitory effects on NO production when evaluated for its effect using macrophages.…”
Section: ⅳ Discussionmentioning
confidence: 99%